Planning and management of educational facilities and infrastructure at the integrated pesantren darul qur'an mulia bogor - Jauhari; Khoirul anam (At Turots: Jurnal Pendidikan Islam, 2024)
This research and observation aims to understand the management of educational facilities and infrastructure to explain and describe: 1) Planning of educational facilities and infrastructure, 2) Procurement of educational facilities and infrastructure, 3) Inventory of educational facilities and infrastructure, 4) Distribution of educational facilities and infrastructure, 5 ) Maintenance of educational facilities and infrastructure. This type of research is a type of descriptive qualitative research, with data collection techniques using observation, interviews and documentation methods. The results of this research show that: 1) Planning for educational facilities and infrastructure needs at the Darul Qur'an Mulia Bogor Integrated Islamic Boarding School has been managed very well and in accordance with the needs of educational institutions; 2) Procurement is of course in accordance with the decision of the Foundation chairman; 3) Inventory activities are carried out once a year and checks are carried out; 4) the distribution of educational facilities and infrastructure carries out a type of signature as proof of distribution of goods; 5) Maintenance of Facilities and Infrastructure is carried out periodically every 3 months; 6) Evaluation is carried out every semester and the evaluation officer is the Acting Officer for Maintenance and Services of facilities and infrastructure